Ethical Behavior of Professional Accountants - Ramljak, Branka; Rogošić, Andrijana; Perica, Ivana (Oeconomica Jadertina, 2017)
Today accounting is an essential system in the developed world since the existing economic system simply cannot function without it. A distinctive feature of the accounting profession is the accepting of responsibility towards the users of accounting information. Every professional accountant, besides being qualified, must have a high degree of professional integrity. Since professional accountants face complex challenges in the business and the professional environment there is an increased stress placed on the ethical behavior of accountants. Ethics and professionalism in accounting are necessary for the accountants as well as for those who use their information. The objectives of this study is to determine whether there is a difference in the level of education of professional accountants according to their sex, are there differences between the sexes when it comes to professionalism and whether the length of service affects their integrity and professionalism. An online survey was conducted in June 2016 and it was sent to 196 e-mail addresses of accountants in Croatia. The results are based on the received feedback from 55 accounting professionals. The obtained results indicate that there is a difference between the sexes due to the level of education. The results also indicate that there is no difference between male and female accountants in relation to their professionalism, and also confirm the influence of experience on the integrity and professionalism of accountants as well as on their ethical behavior.
Keywords: accounting; the accounting profession; professional behavior; accounting ethics; integrity